2020
DOI: 10.3390/su12187666
|View full text |Cite
|
Sign up to set email alerts
|

An Extensive Analysis of Biodiesel Blend Combustion Characteristics under a Wide-Range of Thermal Conditions of a Cooperative Fuel Research Engine

Abstract: Examining the influence of thermal conditions in the engine cylinder at the start of fuel injection on engine combustion characteristics is critically important. This may help to understand physical and chemical processes occurring in engine cycles and this is relevant to both fossil fuels and alternative fuels like biodiesels. In this study, six different biodiesel–diesel blends (B0, B10, B20, B40, B60 and B100 representing 0, 10, 20, 40, 60 and 100% by volume of biodiesel in the diesel–biodiesel mixtures, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…However, it can be concluded that an increase of biodiesel percentage in blends decreases the calorific value of diesel fuel. Similar findings were observed by Nguyen et al (2020) who analysed the biodiesel (B0-B100) blend combustion characteristic under a wide range of thermal condition. The authors state that the high CN of B100 that has more percentage of blends is more reactive and auto-ignites rather than the biodiesel that has low percentage of blends.…”
Section: Torque and Powersupporting
confidence: 86%
“…However, it can be concluded that an increase of biodiesel percentage in blends decreases the calorific value of diesel fuel. Similar findings were observed by Nguyen et al (2020) who analysed the biodiesel (B0-B100) blend combustion characteristic under a wide range of thermal condition. The authors state that the high CN of B100 that has more percentage of blends is more reactive and auto-ignites rather than the biodiesel that has low percentage of blends.…”
Section: Torque and Powersupporting
confidence: 86%
“…A number of papers have studied the characteristics of emissions, performance and combustion of high-ratio biodiesel fuel and pure diesel fuel. The performance and emissions characteristics of biodiesel engines are mainly determined by engine type and its settings, engine emissions control technologies, testing methodology and biodiesel resources [1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, there is a lack of studies investigating the impact of high-ratio biodiesel blends fuel and pure biodiesel (B100) on the performance and emissions of advanced vehicle technologies.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the delay of ignition duration is reduced. In comparison, the combustion behavior is almost similar to the commercial diesel [4]. The shorter ignition delay from using biodiesel fuel leads to the combustion process starting to begin before the engine's optimization point, which is set up by the manufacturer for commercial diesel fuel.…”
Section: Introductionmentioning
confidence: 92%